Wine in the bible : A biblical study on the use of alcoholic beverages - Bacchiocchi, Samuele (Biblical Perspectives, 1989)
WINE IN THE BIBLE is designed to help people to develop strong moral convictions needed to resist the social pressure to drink alcoholic beverages. With painstaking research the book compellingly shows that the Bible consistently teaches total abstinence as a divine imperative. This teaching has been obscured by many modern Bible versions which mistakenly translate as be temperate or be sober, some of the clearest apostolic admonitions to be abstinent. A thoughtful reading of this book may well provoke a revolution in the attitude of many Christians toward alcoholic beverages. WINE IN THE BIBLE is foreworded by three distinguished scholars. One of them is Dr. Robert P. Teachout, Professor of Old Testament at Detroit Baptist Seminary and author of a doctoral dissertation on The Use of Wine in the Old Testament, presented at Dallas Theological Seminary. In his Foreword, Prof. Teachout wrote: Bacchiocchi has done a thorough and convincing job of examining the actual truths of the Biblical teaching on this subject. He has also answered carefully and well the objections of those who disagree with his position. Prof. Stephen Reynolds, one of the translators of the New International Version, and author of two books on the Bible and alcohol, also wrote: I am greatly impressed by the scholarship of WINE IN THE BIBLE which I trust will do much good.